Security evaluation against differential cryptanalysis for dynamic cryptographic structure - Nianping WANG; Zhicheng GUO (Tongxin xuebao)
For CLEFIA cryptographic structure, a dynamic cryptographic structure was put forward.The main feature of the dynamic cryptographic structure was that the diffusion layer in the 6t(t≥1)th round could be selected arbitrarily from some linear bijection on {0,1}4.By analysing the transfer law of 6-round differential characteristic, security evaluation against differential cryptanalysis for all structures of the dynamic cryptographic structure was given.The results show that, under the condition that the round functions are all bijective, there are at least l active round functions for l-round differential characteristic when l is 6k(k≥1) or 6k+1(k≥3), and otherwise there are at least l-1 active round functions for l-round differential characteristic.